2022
DOI: 10.3390/molecules28010150
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric Push–Pull Type Co(II) Porphyrin for Enhanced Electrocatalytic CO2 Reduction Activity

Abstract: Molecular electrocatalysts for electrochemical carbon dioxide (CO2) reduction has received more attention both by scientists and engineers, owing to their well-defined structure and tunable electronic property. Metal complexes via coordination with many π-conjugated ligands exhibit the unique electrocatalytic CO2 reduction performance. The symmetric electronic structure of this metal complex may play an important role in the CO2 reduction. In this work, two novel dimethoxy substituted asymmetric and cross-symm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 54 publications
1
2
0
Order By: Relevance
“…The Tafel slopes (Fig. 3g) for all CoPc/PC- x catalysts were very similar to previous reported values on metal porphyrins and phthalocyanines, 32–34 presenting values much closer to 110 mV dec −1 . The results indicated that the CO 2 RR process over CoPc/PC- x was limited by initial electron–proton transfer to generate a *COOH intermediate.…”
Section: Resultssupporting
confidence: 89%
“…The Tafel slopes (Fig. 3g) for all CoPc/PC- x catalysts were very similar to previous reported values on metal porphyrins and phthalocyanines, 32–34 presenting values much closer to 110 mV dec −1 . The results indicated that the CO 2 RR process over CoPc/PC- x was limited by initial electron–proton transfer to generate a *COOH intermediate.…”
Section: Resultssupporting
confidence: 89%
“…To this end, catalysts based on metal-containing phthalocyanines or porphyrins have been developed, which have demonstrated considerable efficacy for this process [ 140 , 141 , 142 ]. In this regard, Qiu et al [ 143 ] synthesized two novel electrocatalysts for CO 2 reduction by employing dimethoxy-substituted Co(II) porphyrin. The authors suggested that the methoxy group’s electron donor effect facilitated the intramolecular charge transfer, thereby promoting electron mobility.…”
Section: Catalytic Carbon Dioxide Reductionmentioning
confidence: 99%
“…The authors suggested that the methoxy group’s electron donor effect facilitated the intramolecular charge transfer, thereby promoting electron mobility. Furthermore, theoretical calculations using density functional theory (DFT) confirmed that the methoxy group could substantially affect the energy levels of the process, thereby enhancing CO 2 reduction efficiency [ 143 ]. In another study, Shi et al [ 144 ] synthesized a hybrid cobalt(II) phthalocyanine-COOH/carbon nanotube (CNT) catalyst by anchoring CoPc-COOH onto the surface of carbon nanotubes.…”
Section: Catalytic Carbon Dioxide Reductionmentioning
confidence: 99%